Jig Design for Welding of Wind Power Plant Component - Mrkvica, Ivan; Dihel, Kamil; Szotkowski, Tomas; Jurko, Jozef; Panda, Anton (Manufacturing Technology Journal, 2017)
Article deals with design of welding jig for assembly of wind power plant component. Mainstay of article is design of welding jig, which makes exactly setting and reliable clamping of individual parts of welded desing possible for their complete welding. Design procedure of individual parts of welding jig is described in details in view of their functionality. Paper is especially focused on the parts of welding jig, which are necessary to make, including material selection of individual parts. Finally the technical and economic evaluation is carried out, approximate cost of jig is calculated and financial savings associated with practical use of welding jig are evaluated.
Keywords: welding jig; basic board; setting and clamping; vertical clamp